TEACHER EDUCATION IN CAMBODIA: FORMULAE, CHALLENGES, AND SUGGESTIONS FOR IMPROVEMENT - Sereyrath Em; Pisith Chin; Somphors Khan; Nel Nun (Asosiasi Dosen Perguruan Tinggi Islam, 2022)
Education is the key to building human capital in all countries in the world. Without enough qualified individuals, no country can be properly developed. Therefore, teacher education is essential in all countries. All kinds of development processes emerge from learning and teaching. A teacher is the most important character in building human capital. So, teacher education is even more important. Cambodia has a very long history of education. Education in this country used to reach the top during the Angkor Period and dropped down to zero during the Killing Fields. This article reviews some aspects of education, the formulae of teacher education after year zero, and the challenges of teacher education, and it also suggests some ideas to improve the teacher education process in Cambodia. This research is qualitative research with a documentary study approach. This article shows that education in Cambodia used to peak and fall to zero.